Fabrication and Performance Analysis of Novel HTV Silicon Rubber Nanocomposites for High Voltage Insulation in Outdoor Environment - Aqeel Ur Rehman; Muhammad Salman Khan; Abraiz Khattak; Yasin Khan; Khalid Hamad Alkhalid (IEEE Access)
Silicon rubber incorporated with nano silica with a wide range of percentages has been investigated for the performance analysis of high voltage insulation. Electrical power systems need robust and long-term high-performance insulation. Polymeric insulators have revolutionized electrical power system insulations with their lightweight and high mechanical endurance. Adding silica as an inorganic filler has enhanced electrical, mechanical, and thermal properties with variations among the specific ranges. Fabrication of silicon rubber nanocomposites was accomplished by a highly accurate procedure that included extensive testing with rubber technology. The extraordinarily high resistive nature of silicon rubber nanocomposites displays the insulation levels attained by nano-filler addition to the base matrix. The most considerable band gap energy was found in Silicone Rubber with 1% silica nano-composite filling, followed by 3% and 7% nanocomposites with an improvement of 71% and 76%, respectively. 1% silica nanocomposites have the highest DC resistance value among all nanocomposites. The lowest DC resistance was noticed in 5% silica-filled nanocomposites with 134.5G $Ω $ at 60°. At the same time, 3% silica-filled samples showed the highest stability under mechanical and thermal stresses. This research was performed at the High Voltage Laboratory, National University of Sciences & Technology, Pakistan. Performance analysis of nanocomposites has been personated with an extensive improvement in insulating regions and lower values of partial discharge behaviors when electric stress is applied. Mechanical and thermal characterization of nanocomposites shows that silica has strengthened the silicon rubber structure for resilient and long-term insulation behaviors in outdoor environments.